EFFECT OF AN EXERCISE PROGRAM USING THERA-BAND ON LEG AND JOINT MOBILITY IN PATIENTS WITH KNEE OSTEOARTRITIS - Thammakongthong, Siriwan; Abdullakasim, Pajaree; Maharachpong, Nipa (Journal of Public Health Nursing, 2019)
Knee osteoarthritis is an important public health problem. Knee osteoarthritis often results in knee pain, stiffness and a decrease in joint function. Patients experience a decrease in quality of life. The purpose of this quasi-experimental research was to study the effect of an exercise program using the thera-band exercise, the Health Belief Model (HBM) and Social Support (SS) for patients with knee osteoarthritis. Subjects were 40 patients, aged 50 – 65 years old divided into two groups of 20 patients each. The experimental group received a health education and exercise program with thera-band exercise performed 3 days/week for 6 weeks. Research instruments included a researcher-developed questionnaire based on HBM and SS for exercise behavior which was used at pre- and post-test (after 6 weeks). The Modified WOMAC Thai index was used to assess joint function at pre-test and every week. Range of motion (ROM) of the knee was measured by Goniometer at pre- and post-test. After the program, the experimental group had a significantly increased mean score of HBM and SS (p < 0.001) with the Modified WOMAC Thai index showing a significant decrease (p < 0.001) compared to the pre-test and the comparison group. ROM was also significantly improved (p < 0.001). While exercise behavior did not show a significant difference (p = 0.186), the thera-band exercise program may be a better choice for basic exercise treatment in knee osteoarthritis.